Low-temperature heat-sealing packaging composite film easy to recycle and preparation process

By mixing low -melting points in the sauce packaging material, Maojinsin belongs to polyethylene and hydrophoblate polymer to prepare the easy recycling low -heating packaging composite film to solve the problem of insufficient adhesion and thermal sealing strength. Achieve efficient heat sealing and anti -adhesive effects.

CN119348278AActive Publication Date: 2025-01-24SUZHOU ZIJIN PLASTIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411451520.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

During the use of existing sauce packaging materials, the problem of the sauce sticking to the surface of the packaging materials is prone to waste. At the same time, the traditional heat seal film lacks heat sealing strength at low temperatures.

Method used

By mixing low -melting points in the polyethylene, it is used to optimize the hydrophobic performance with hydrophobic silicone polymer to optimize the hydrophobic performance to prepare a composite film that is easy to recycle low temperature packaging packaging. This composite film adopts the film structure of the eleven layer of the co -squeezing membrane, including the surface layer, support layer, bonding layer, blocking layer, thermal seal layer, etc., and is prepared through joint squeezing and blowing film.

Benefits of technology

The packaging composite film achieves a heat sealing strength greater than 15N/15mm under low-temperature heat sealing conditions of 100°C, significantly reduces the adhesion of sauce on the surface of the packaging composite film, and has good anti-stick properties and easy recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119348278A_ABST
    Figure CN119348278A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of research and development of multifunctional sauce packaging materials, in particular to an easy-to-recover low-temperature heat-seal packaging composite film and a preparation process thereof, and the preparation process comprises the following steps: setting the packaging composite film as an eleven-layer co-extrusion film; the preparation method comprises the following steps: carrying out crosslinking treatment on hydroxyl-terminated polydimethylsiloxane by utilizing a silane crosslinking agent containing a phenolic hydroxyl functional group and a methoxyl functional group to prepare an anti-sticking modifier; metallocene polyethylene resin, low-density polyethylene resin and an anti-sticking modifier are used as raw materials to synthesize a heat sealing layer, an eleven-layer co-extrusion blow molding film forming process is adopted, and the low-temperature heat-sealing packaging composite film easy to recover and with the thickness being 50-200 microns is prepared. And moreover, the beneficial technical effect that the heat sealing strength is greater than 15N / 15mm is achieved at the low-temperature heat sealing of 100 DEG C, the effects of saving energy and reducing consumption are achieved in the packaging link, and the sauce packaging film can be used for packaging sauce products and plays a role in preventing adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of research and development of multifunctional sauce packaging materials, and in particular to an easily recyclable low-temperature heat-sealed packaging composite film and a preparation process thereof. Background Art

[0002] Sauce is a kind of daily seasoning product, which is mostly used to add color and flavor in diet and cooking. Sauces are packaged in various forms, including canned packaging and easy-to-carry bag packaging. Bag-packed sauces are mostly packaged in plastic soft film.

[0003] The emergence of small-bag packaged sauces is the result of market demand. It can provide consumers with various conveniences. Compared with large canned sauces that are large in size and difficult to carry, small-bag packaged sauces are more suitable for use in small quantities such as traveling and fast food. This has led to a high usage of sauce bags. With the increase in usage, the problems arising during use have also become prominent. A typical manifestation is that as a viscous liquid food, a lot of sauce will always adhere to the surface of the packaging material after consumption, causing waste.

[0004] In addition, heat sealing uses external heating conditions (electric heating, high-frequency induction heating, ultrasonic waves, etc.) to make the sealing part of the plastic substrate film become a viscous flow state, and with the help of the pressure between the heat sealing cutters, the upper and lower layers of the film are fused into one, and a certain strength is maintained after cooling. The factors that affect the heat sealing properties of the film are mainly the melting point of the film. Films with low melting points generally require lower temperatures when heat-sealed. Among several commonly used heat-sealing films, EVA films, ionomers and metallocene polyethylene have lower heat-sealing temperatures than PE films. Among them, the melting point of metallocene polyethylene is lower than that of traditional polyethylene, so at the same density, its heat-sealing temperature is also lower, but the heat-sealing strength is higher.

[0005] In addition, packaging materials made of a single material do not need to be sorted when recycled and can be recycled repeatedly, which is gradually becoming an industry development trend for plastic flexible packaging. Summary of the invention

[0006] The present invention uses hydrophobic siloxane polymers to optimize the hydrophobic properties of a polyethylene matrix, and on the other hand optimizes the low-temperature heat-sealing properties of a polyethylene matrix by blending low-melting-point metallocene polyethylene. An easily recyclable low-temperature heat-sealing packaging composite film is prepared by a co-extrusion blow molding film-forming process.

[0007] A preparation process of an easily recyclable low-temperature heat-sealed packaging composite film comprises the following steps:

[0008] Step 1: setting a film layer structure of an eleven-layer co-extruded film, wherein the structure is as follows: surface layer (6-1), support layer (5-1), support layer (4-1), adhesive layer (3-1), barrier layer (2-1), barrier layer (1), barrier layer (2-2), adhesive layer (3-2), support layer (4-2), support layer (5-2), and heat-sealing layer (6-2);

[0009] Step 2: Prepare the raw materials for the eleven-layer co-extrusion film:

[0010] The raw materials of the surface layer (6-1) are 60-80 wt% of low-density polyethylene resin and 20-40 wt% of linear low-density polyethylene resin;

[0011] The raw materials of the support layer (5-1), the support layer (4-1), the support layer (5-2) and the support layer (4-2) are all 30-50wt% of high-density polyethylene resin and 50-70wt% of low-density polyethylene resin;

[0012] The raw materials of the adhesive layer (3-1) and the adhesive layer (3-2) are both 100 wt% maleic anhydride grafted polyethylene resin;

[0013] The raw materials of the barrier layer (2-1) and the barrier layer (2-2) are 95-99 wt% of low-density polyethylene resin and 1-5 wt% of ethylene-vinyl alcohol copolymer resin;

[0014] The raw materials of the barrier layer (1) are 90-99 wt% of low-density polyethylene resin and 1-10 wt% of ethylene-vinyl alcohol copolymer resin;

[0015] The raw materials of the heat seal layer (6-2) are 15-25wt% of low-density polyethylene resin, 65-85wt% of metallocene polyethylene resin and 1-10wt% of anti-sticking modifier;

[0016] The preparation method of the anti-sticking modifier is as follows: cross-linking the hydroxyl-terminated polydimethylsiloxane with a silane cross-linking agent containing a phenolic hydroxyl functional group and a methoxy functional group;

[0017] Step 3: According to the formula raw materials in step 2, an eleven-layer co-extrusion blow molding film-forming process is adopted to prepare an easily recyclable low-temperature heat-sealed packaging composite film with a thickness of 50 to 200 μm.

[0018] Preferably, the mass ratio of the surface layer (6-1), the support layer (5-1), the support layer (4-1), the adhesive layer (3-1), the barrier layer (2-1), the barrier layer (1), the barrier layer (2-2), the adhesive layer (3-2), the support layer (4-2), the support layer (5-2), and the heat-sealing layer (6-2) in the packaging composite film is (5-15): (5-15): (5-15): (1-5): (5-15): (3-10): (5-15): (1-5): (5-15): (5-15): (10-30).

[0019] Preferably, the preparation method of the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups is: a basic catalyst is used to catalyze the nucleophilic addition reaction of 1 molar equivalent of the alkenyl functional group of magnolol with (2.01-2.05) molar equivalents of the mercapto functional group of 3-mercaptopropyltrimethoxysilane to obtain a silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups.

[0020] Preferably, the alkaline catalyst is one of sodium hydroxide, sodium carbonate and sodium ethoxide.

[0021] Preferably, the preparation method of the anti-sticking modifier is: on the one hand, the hydrolysis functional groups of the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups are used to generate silanol functional groups that undergo a hydrolysis reaction and the hydroxyl functional groups of the hydroxyl-terminated polydimethylsiloxane undergo a condensation reaction; on the other hand, the phenolic hydroxyl functional groups of the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups are used to generate hydrogen bonds with the hydroxyl-terminated polydimethylsiloxane to prepare the anti-sticking modifier.

[0022] Preferably, the mass ratio of the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups to the hydroxyl-terminated polydimethylsiloxane in the anti-sticking modifier is 1:(2-10).

[0023] Preferably, the number average molecular weight of the hydroxyl-terminated polydimethylsiloxane is 1000-4000.

[0024] The easily recyclable low-temperature heat-sealing packaging composite film prepared according to the above process has a heat-sealing strength of ≥15N / 15mm under the condition of a heat-sealing temperature of 100°C.

[0025] The easily recyclable low-temperature heat-sealed packaging composite film prepared according to the above process is used for packaging sauce products and plays an anti-adhesion role.

[0026] Beneficial effects:

[0027] A silane cross-linking agent containing both phenolic hydroxyl and methoxy functional groups was synthesized using magnolia ol, a biologically active compound extracted from Magnolia officinalis bark, and 3-mercaptopropyltrimethoxysilane as raw materials. The silane cross-linking agent was used to cross-link hydroxyl-terminated polydimethylsiloxane (hydrophobic agent). The cross-linked silane was then added to polyethylene containing metallocene polyethylene (low-temperature heat-sealing resin) in the formula to prepare a packaging composite film. The film not only significantly reduced the amount of sauce adhered to the surface of the packaging composite film, but also achieved a beneficial technical effect of a heat-sealing strength greater than 15N / 15mm under low-temperature heat sealing at 100°C, which has an energy-saving and consumption-reducing effect in the packaging link. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the product structure diagram of the packaging composite film;

[0029] Among them, numbers 1, 2-1 and 2-2 are barrier layers, numbers 3-1 and 3-2 are adhesive layers, numbers 4-1, 4-2, 5-1 and 5-2 are support layers, number 6-1 is a surface layer, and number 6-2 is a heat-sealing layer. DETAILED DESCRIPTION

[0030] Embodiment 1:

[0031] Preparation of a silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups: A basic catalyst catalyzes a nucleophilic addition reaction between the alkenyl functional group of 1 molar equivalent of magnolol and the mercapto functional group of (2.01-2.05) molar equivalents of 3-mercaptopropyltrimethoxysilane to generate a silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups, the chemical structure of which is:

[0032]

[0033] The alkaline catalyst is one of sodium hydroxide, sodium carbonate and sodium ethoxide; sodium ethoxide is selected in this experimental example;

[0034] The specific experimental steps for preparing the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups are as follows: 2.7 g of magnolol, 0.5 g of sodium ethoxide and 30 mL of anhydrous ethanol are added to a three-necked flask, stirred at room temperature until all dissolved, then 4 mL of 3-mercaptopropyltrimethoxysilane is added dropwise to the three-necked flask, the temperature is raised to 70° C. and stirred for reaction for 6 h, cooled to room temperature, washed with deionized water, dried with anhydrous magnesium sulfate, rotary evaporated to remove the solvent, and vacuum dried to obtain a silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups;

[0035] The nuclear magnetic resonance hydrogen spectrum of the silane crosslinker containing phenolic hydroxyl functional groups and methoxy functional groups is characterized as follows: 1 H NMR (CDCl 3, 400MHz) δ: 0.78-0.82 (t, 4H), 1.65-1.72 (m, 4H), 1.85-1.92 (m, 4H), 2.5 2-2.58(m, 8H), 2.82-2.86(t, 4H), 3.57(s, 18H), 6.90-7.09(m, 6H, Ar-H).

[0036] Embodiment 2:

[0037] The anti-sticking modifier is prepared by a method of: cross-linking hydroxyl-terminated polydimethylsiloxane using a silane cross-linking agent containing a phenolic hydroxyl functional group and a methoxy functional group to prepare the anti-sticking modifier;

[0038] The cross-linking mechanism of the silane cross-linking agent containing phenolic hydroxyl functional groups and methoxy functional groups on the hydroxyl-terminated polydimethylsiloxane is as follows: on the one hand, the hydrolysis functional groups of the silane cross-linking agent undergo a hydrolysis reaction to generate silanol functional groups that undergo a condensation reaction with the hydroxyl functional groups of the hydroxyl-terminated polydimethylsiloxane; on the other hand, the phenolic hydroxyl functional groups of the silane cross-linking agent produce hydrogen bonds with the hydroxyl-terminated polydimethylsiloxane;

[0039] The specific experimental steps for preparing the anti-sticking modifier are as follows: 5 g of hydroxyl-terminated polydimethylsiloxane, 80 mL of dichloromethane and 20 mL of deionized water are added to a beaker, the temperature is raised to 40° C. and stirred until all are evenly dissolved, then 1 g of a silane crosslinker containing a phenolic hydroxyl functional group and a methoxy functional group and 2 drops of glacial acetic acid are added to the beaker in sequence, the temperature is continued to be raised to 60° C. and stirred for reaction for 5 h, the temperature is cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum drying is performed to obtain the anti-sticking modifier;

[0040] Among them, hydroxyl-terminated polydimethylsiloxane was purchased from Wuhan Kemik Biomedical Technology Co., Ltd., and its specification is: average Mn~2000.

[0041] Embodiment 5:

[0042] Preparation of packaging composite film: Using an eleven-layer co-extrusion film blowing unit, a packaging composite film with a thickness of 80 μm was prepared, such as Figure 1 As shown, the film structure of the packaging composite film is: surface layer 6-1, support layer 5-1, support layer 4-1, adhesive layer 3-1, barrier layer 2-1, barrier layer 1, barrier layer 2-2, adhesive layer 3-2, support layer 4-2, support layer 5-2, heat sealing layer 6-2, and the mass ratio based on the film structure is 10:10:10:2.5:10:5:10:2.5:10:10:20;

[0043] The raw materials of the surface layer 6-1 are 70wt% low-density polyethylene resin and 30wt% linear low-density polyethylene resin; the raw materials of the support layer 5-1, support layer 4-1, support layer 5-2 and support layer 4-2 are all 40wt% high-density polyethylene resin and 60wt% low-density polyethylene resin; the raw materials of the heat-sealing layer 6-2 are 20wt% low-density polyethylene resin, 75wt% metallocene polyethylene resin and 5wt% anti-sticking modifier;

[0044] The process parameters of the screw extruder corresponding to the surface layer 6-1, the support layer 5-1, the support layer 4-1, the support layer 5-2, the support layer 4-2 and the heat sealing layer 6-2 are all set as follows: the temperature of the 1-3 zones is 120°C, 150°C and 170°C respectively, the flow channel temperature is 165°C, and the rotation speed is 30r / min;

[0045] The raw materials of barrier layer 1 are 95wt% low-density polyethylene resin and 5wt% ethylene-vinyl alcohol copolymer resin, and the corresponding process parameters of the screw extruder are set as follows: the temperatures of zones 1-3 are 150°C, 170°C, and 190°C, respectively, the flow channel temperature is 185°C, and the rotation speed is 40r / min;

[0046] The raw materials of barrier layer 2-1 and barrier layer 2-2 are both 97wt% low-density polyethylene resin and 3wt% ethylene-vinyl alcohol copolymer resin, and the corresponding process parameters of the screw extruder are set as follows: the temperatures of zones 1-3 are 140°C, 160°C, and 180°C, respectively, the flow channel temperature is 175°C, and the rotation speed is 40r / min;

[0047] The raw materials of the adhesive layer 3-1 and the adhesive layer 3-2 are both 100wt% maleic anhydride grafted polyethylene resin, and the corresponding process parameters of the screw extruder are set as follows: the temperatures of zones 1-3 are 115°C, 145°C, and 160°C, respectively, the flow channel temperature is 150°C, and the rotation speed is 15r / min;

[0048] Among them, low-density polyethylene resin was purchased from Jiangsu Rantai Plastic Co., Ltd. with the brand name LD 150DW; linear low-density polyethylene resin was purchased from Yuyao Hongyang Plastic Co., Ltd. with the brand name 2045G; high-density polyethylene resin was purchased from Dongguan Longhuang Plastic Raw Materials Co., Ltd. with the brand name FB5600; metallocene polyethylene resin was purchased from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd. with the brand name SP4020; maleic anhydride grafted polyethylene resin was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd. with the brand name 4288.

[0049] Comparative Example:

[0050] Preparation of composite film a: Referring to the preparation experiment of the packaging composite film, the only difference is that no anti-sticking modifier is used to prepare the composite film a, which is used as comparative example 1;

[0051] Preparation of composite film b: Referring to the preparation experiment of packaging composite film, the only difference is that no anti-sticking modifier is used, and the raw material of heat sealing layer 6-2 is 100wt% low-density polyethylene resin, to prepare composite film b, which is used as comparative example 2.

[0052] Performance Testing:

[0053] (1) Heat sealing performance test: The heat sealing test was carried out on the samples using a HSG-C heat sealer, with a sealing knife area of ​​15 cm × 1 cm, a heat sealing temperature of 100°C, a heat sealing pressure of 0.2 MPa, and a heat sealing time of 2.0 s. The heat sealing performance of the samples was tested in accordance with QB / T 2358-1998;

[0054] (2) Barrier performance test: The barrier performance of the samples was tested according to GB / T 1038-2000 and GB / T 1037-2021 respectively;

[0055] (3) Mechanical properties test: The mechanical properties of the samples were tested according to GB / T 13022-91;

[0056] (4) Anti-sticking performance test: The anti-sticking performance is analyzed by testing the residual amount of sauce on the sample. The specific test steps are as follows: fix a 3 cm × 2 cm sample on a 5 cm × 4 cm long × wide plywood, inject a drop of sauce (Zuo Xiangyuan soybean sauce) onto the top of the sample with a syringe filled with sauce and a range of 20 mL, weigh the initial sauce mass, and then place the test sample at an angle of 45° to the horizontal plane. After the sauce flows down, let it stand for 20 seconds, record the remaining sauce mass after tilting, and calculate the sauce residue. The specific method is as follows:

[0057] Sauce residue (%) = the mass of sauce remaining on the sample after tilting / the mass of sauce initially on the sample;

[0058] (5) Hygienic performance: The hygienic performance of the samples was tested in accordance with GB / T 5009.60-2003;

[0059] The above test results are shown in Tables 1 and 2;

[0060] Table 1 Performance test results of packaging composite film

[0061]

[0062] Table 2 Performance test results of composite membrane II

[0063]

[0064] Note: The physical and chemical indicators of the experimental results are based on GB / T 5009.58-2003 "Analysis Methods for Hygienic Standards of Polyethylene Resins for Food Packaging";

[0065] By comprehensively analyzing the above experimental results, the following conclusions can be drawn:

[0066] Conclusion 1: The heat sealing strength of the packaging composite film prepared by the present invention is greater than 15N / 15mm under the condition of a heat sealing temperature of 100°C. Referring to national standards and the use requirements of enterprise users, the packaging composite film prepared by the present invention belongs to a low-temperature heat-sealing packaging material;

[0067] Conclusion 2: The anti-sticking modifier prepared by cross-linking hydroxyl-terminated polydimethylsiloxane with a silane cross-linking agent containing phenolic hydroxyl functional groups and methoxy functional groups can significantly reduce the amount of sauce residue in the packaging composite film, and has a very significant effect on improving the anti-sticking properties of the packaging composite film;

[0068] Conclusion 3: The packaging composite film prepared by the present invention exhibits relatively excellent barrier properties and mechanical properties.

Claims

1. A process for preparing an easily recyclable low-temperature heat-sealed packaging composite film, characterized in that: The following steps are involved: Step 1: setting a film layer structure of an eleven-layer co-extruded film, wherein the structure is as follows: surface layer (6-1), support layer (5-1), support layer (4-1), adhesive layer (3-1), barrier layer (2-1), barrier layer (1), barrier layer (2-2), adhesive layer (3-2), support layer (4-2), support layer (5-2), and heat-sealing layer (6-2); Step 2: Prepare the raw materials for the eleven-layer co-extrusion film: The raw materials of the surface layer (6-1) are 60-80 wt% of low-density polyethylene resin and 20-40 wt% of linear low-density polyethylene resin; The raw materials of the support layer (5-1), the support layer (4-1), the support layer (5-2) and the support layer (4-2) are all 30-50wt% of high-density polyethylene resin and 50-70wt% of low-density polyethylene resin; The raw materials of the adhesive layer (3-1) and the adhesive layer (3-2) are both 100 wt% maleic anhydride grafted polyethylene resin; The raw materials of the barrier layer (2-1) and the barrier layer (2-2) are 95-99 wt% of low-density polyethylene resin and 1-5 wt% of ethylene-vinyl alcohol copolymer resin; The raw materials of the barrier layer (1) are 90-99 wt% of low-density polyethylene resin and 1-10 wt% of ethylene-vinyl alcohol copolymer resin; The raw materials of the heat seal layer (6-2) are 15-25wt% of low-density polyethylene resin, 65-85wt% of metallocene polyethylene resin and 1-10wt% of anti-sticking modifier; The preparation method of the anti-sticking modifier is as follows: cross-linking the hydroxyl-terminated polydimethylsiloxane with a silane cross-linking agent containing a phenolic hydroxyl functional group and a methoxy functional group; The chemical structural formula of the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups is: Step 3: According to the formula raw materials in step 2, an eleven-layer co-extrusion blow molding film-forming process is adopted to prepare an easily recyclable low-temperature heat-sealed packaging composite film with a thickness of 50 to 200 μm.

2. The process for preparing an easily recyclable low-temperature heat-sealable packaging composite film according to claim 1, characterized in that: The mass ratio of the surface layer (6-1), the support layer (5-1), the support layer (4-1), the adhesive layer (3-1), the barrier layer (2-1), the barrier layer (1), the barrier layer (2-2), the adhesive layer (3-2), the support layer (4-2), the support layer (5-2), and the heat-sealing layer (6-2) in the packaging composite film is (5-15): (5-15): (5-15): (1-5): (5-15): (3-10): (5-15): (1-5): (5-15): (5-15): (10-30).

3. The process for preparing an easily recyclable low-temperature heat-sealable packaging composite film according to claim 1, characterized in that: The preparation method of the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups is as follows: a basic catalyst is used to catalyze a nucleophilic addition reaction between 1 molar equivalent of the alkenyl functional group of magnolol and (2.01-2.05) molar equivalents of the mercapto functional group of 3-mercaptopropyltrimethoxysilane to obtain the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups.

4. The process for preparing an easily recyclable low-temperature heat-sealable packaging composite film according to claim 3, characterized in that: The alkaline catalyst is one of sodium hydroxide, sodium carbonate and sodium ethoxide.

5. The process for preparing an easily recyclable low-temperature heat-sealable packaging composite film according to claim 1, characterized in that: The preparation method of the anti-sticking modifier comprises the following steps: on one hand, hydrolysis reaction of the hydrolysis functional group of the silane crosslinking agent containing the phenolic hydroxyl functional group and the methoxyl functional group generates the silanol functional group and the hydroxyl functional group of the hydroxyl-terminated polydimethylsiloxane to undergo a condensation reaction; and on the other hand, hydrogen bonding is generated between the phenolic hydroxyl functional group of the silane crosslinking agent containing the phenolic hydroxyl functional group and the methoxyl functional group and the hydroxyl-terminated polydimethylsiloxane to prepare the anti-sticking modifier.

6. The process for preparing an easily recyclable low-temperature heat-sealable packaging composite film according to claim 5, characterized in that: The mass ratio of the silane crosslinking agent containing phenolic hydroxyl functional groups and methoxy functional groups to the hydroxyl-terminated polydimethylsiloxane in the anti-sticking modifier is 1:(2-10).

7. The process for preparing an easily recyclable low-temperature heat-sealable packaging composite film according to claim 5, characterized in that: The number average molecular weight of the hydroxyl-terminated polydimethylsiloxane is 1000-4000.

8. An easily recyclable low-temperature heat-sealable packaging composite film prepared by the process according to any one of claims 1 to 7, characterized in that: The packaging composite film has a heat sealing strength of ≥15N / 15mm under the condition that the heat sealing temperature is 100°C.

9. The easily recyclable low-temperature heat-sealable packaging composite film according to claim 8, characterized in that: The packaging composite film is used for packaging sauce products and plays an anti-adhesion role.

Citation Information

Patent Citations

  • UV light-cured resin composition as well as preparation method and application thereof

    CN113943420A

  • High-voltage cable electromagnetic shielding composite material and preparation process thereof

    CN116836476A